Freshwater prawns of the genus Macrobrachium Bate, 1868 (Crustacea: Decapoda: Palaemonidae) of Colombia - Valencia, Diego M.; Campos, Martha R. (Zootaxa, 2007)
A review of the species of freshwater prawns belonging to the genus Macrobrachium in Colombia is presented. According to the study, the genus Macrobrachium comprises 20 species for Colombia. The species Macrobrachium cortezi Rodríguez, 1982, M. ferreirai Kensley & Walker, 1982 and M. reyesi Pereira, 1986 are recorded for the first time in the country. Geographical species distributions are updated with basis on new material. Diagnoses, illustrations and a key for Colombian Macrobrachium species are included.